Nitrogen derived from fertilization and straw for plant cane nutrition - Vitti, André Cesar; Junqueira Franco, Henrique Coutinho; Trivelin, Paulo Cesar Ocheuze; Ferreira, Danilo Alves; Otto, Rafael; Fortes, Caio; Faroni, Carlos Eduardo (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the recovery, by plant cane, of the nitrogen (15N) from urea and from sugarcane (Saccharum spp.) crop residues – straw and root system – incorporated into the soil. The experiment was settled in 2005/2006 with the sugarcane cultivar SP81 3250. At planting, microplots of 2 m length and 1.5 m width were installed, and N applications were done with 80 kg ha-1 N (urea with 5.05% in 15N atoms) and 14 Mg ha-1 crop residues – 9 Mg ha-1 of sugarcane straw (SS) and 5 Mg ha-1 of root system (RS), labeled with 15N (1.07 and 0.81% in 15N atoms, respectively). The total N accumulation by plants was determined during the crop cycle. Although the N use by shoot from crop residue mineralization (PA and SR) increased significantly over time, this source hardly contributed to crop nutrition. The recovery of the 15N-urea, 15N-SS and 15N-RS by plant cane was 30.3±3.7%, 13.9±4.5% and 6.4±0.9%, respectively, representing 15.9, 4.7 and 1.4% of total nitrogen uptake by shoot.